Влияние взаимного расположения резцов на энергоемкость разрушения прочной горной породы - Свешников, И.А.; Майстренко, А.Л.; Заболотный, С.Д.; Беспалов, С.Ф.; Доброскокин, А.И.; Городецкий, В.Г.; Осадчук, Н.П. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
It is experimentally established, that the tool of ISM design effectively works to depth of cutting of 8 mm., thus minimum power consumption of destruction of breed is observed at a step of
cutting Тр = 60 mm. Necessary Тр the mathematical model is developed for the computer program
of arrangement of cutters in a combine crown